Association of regional anesthesia with oncological outcomes in patients receiving surgery for bladder cancer: A meta-analysis of observational studies - Illias, Amina M.; Yu, Kai-Jie; Wu, Shao-Chun; Cata, Juan P.; Tsai, Yung-fong; Hung, Kuo-Chuan (Frontiers in Oncology, 2023)
Background: This meta-analysis was conducted to compare cancer recurrence and survival rates in patients with bladder cancer receiving surgery under general anesthesia alone (i.e., GA group) or regional anesthesia (RA) with or without GA (i.e., RA±GA group) Methods: Literature search on Cochrane library, EMBASE, Google scholar, and Medline databases was performed to identify all relevant studies from inception to April 30, 2022. The primary outcome was cancer recurrence rate, while the secondary outcomes included overall survival rate and cancer-specific survival rate. Subgroup analyses were performed based on study design [(Propensity-score matching (PSM) vs. no-PSM)] and type of surgery [transurethral resection of bladder tumor (TURBT) vs. radical cystectomy]. Results: Ten retrospective studies with a total of 13,218 patients (RA±GA group n=4,884, GA group n=8,334) were included. There was no difference between RA±GA group and GA group in age, the proportion of males, severe comorbidities, the proportion of patients receiving chemotherapy, and the pathological findings (all p >0.05). Patients in the RA±GA group had significantly lower rate of bladder cancer recurrence [odds ratio (OR): 0.74, 95%CI: 0.61 to 0.9, p=0.003, I2=24%, six studies] compared to those in the GA group. Subgroup analyses based on study design revealed a consistent finding, while the beneficial effect of RA±GA on reducing cancer recurrence was only significant in patients receiving TURBT (p=0.02), but not in those undergoing radical cystectomy (p=0.16). There were no significant differences in overall survival rate and cancer-specific survival rate between RA±GA and GA groups. Conclusions: For patients receiving surgery for bladder cancer, the application of regional anesthesia with or without general anesthesia is associated with significant decrease in cancer recurrence, specially in patients undergoing TURBT for non-muscle invasive bladder cancer. Because of the limited number of studies included and potential confounding factors, our results should be interpreted carefully.